PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP 1 SINGINGI KELAS JAUH KEBUN LADO - Indah Noviani Ulfa; Susda Heleni; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve learning process and the student’s mathematics learning outcomes through implementation of Problem Based Learning (PBL) Model. This research is Classroom Action Research conducted in class VII SMP 1 Singingi Kelas Jauh Kebun Lado in the even semester of the academic year 2018/2019. The subject of this research consist of 20 students. The research consist of two cycles, each cycle have four stages. The research instrument consists of learning materials and instruments for collecting data. Learning materials used in this research are the syllabus, Lesson Plan and Activity Sheets. The instruments of data collection and students mathematic tests. The observation sheets is analyzed in qualitative desciptive, while the students mathematic tests is analyzed in quantitative descriptive. The qualitative descriptive show an improvement of learning process prior to the action on the first and second cycle. The results of this study indicate the number of students who reached Minimum Mastery Criteria of knowledge increase from basic score to first test and second test. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (35%) to the first test (65%) to the second test (85%). For the skills of the first test (60%) to the second test (75%). From these data it can be concluded that the application of Problem Based Learning can increase mathematics achievement from the students at class VII SMP 1 Singingi Kelas Jauh Kebun Lado in academic years 2018/2019 .Key Words: Problem Based Learning model, Mathematics Learning Outcomes